2014
DOI: 10.1115/1.4028052
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Hemodynamics in Tortuous Left Coronary Artery: A Morphological Parametric Study

Abstract: Coronary tortuosity (CT) would alter the local wall shear stress (WSS) and may become a risk factor for atherosclerosis. Here we performed a systematic computational study to relate CT morphological parameters to abnormal WSS, which is a predisposing factor to the formation of atherosclerotic lesions. Several idealized left coronary artery (LCA) models were created to conduct a series of morphological parametric studies, in which we concentrate on three specific morphological parameters, the center line radius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…A decrease in the fluid-solid coupled interaction might explain the severely disturbed flow in the SHR-NIF group, which was consistent with previous findings of significantly increasing turbulent kinetic energy in an ideal rigid ascending aorta model 6 . These findings indicated that the decreased interaction in artery regions might contribute to spatial susceptibility to lesions formation in hypertensive and antihypertensive individuals regardless of the drop in BP, especially in arteries with high tortuosity or bifurcations 21 . Reducing this increased risk required interventions, drugs or exercise, to directly improve vascular remodelling.…”
Section: Discussionmentioning
confidence: 85%
“…A decrease in the fluid-solid coupled interaction might explain the severely disturbed flow in the SHR-NIF group, which was consistent with previous findings of significantly increasing turbulent kinetic energy in an ideal rigid ascending aorta model 6 . These findings indicated that the decreased interaction in artery regions might contribute to spatial susceptibility to lesions formation in hypertensive and antihypertensive individuals regardless of the drop in BP, especially in arteries with high tortuosity or bifurcations 21 . Reducing this increased risk required interventions, drugs or exercise, to directly improve vascular remodelling.…”
Section: Discussionmentioning
confidence: 85%
“…The TAWSS and the OSI are defined as where τ W is the WSS vector and T is the cardiac cycle. The OSI can reach a maximum value of 0.5 in regions with the high oscillating shear stress indicating the greater susceptibility of these regions to develop atherosclerosis [5,7,23,42]. Figure 3a, b demonstrates the WSS at the moments of late diastole and peak systole in the cardiac cycle over the endothelial surface of the healthy thoracic aorta.…”
Section: Wss-derived Parametersmentioning
confidence: 95%
“…However, the role of high wall shear stresses on the plaque rupture and atherothrombosis has been widely accepted [3,4,12,29]. Accurate knowledge of stresses developed in both healthy and diseased vessels is critical in analyzing biomechanical determinants of plaque rupture [3,29,42]. Therefore, we quantify the hemodynamics for moderate and severe stenosed aortic arch and its branches to demonstrate the impact of plaque location and size to the high stress magnitude.…”
mentioning
confidence: 98%
“…These patients also had more angina crises (p < 0.05). 44 The only retrospective study on the theme was done by a Chinese team, and included 48 patients with angina chest pains who underwent myocardial scintigraphy and coronarography, and exclusion criteria included individuals with obstructive coronary disease, myocardial bridge, coronary spasm, coronary fistula, hypertrophic cardiomyopathy, myocarditis, and aortic stenosis.…”
Section: Relation To Myocardial Ischemiamentioning
confidence: 99%